THE PROBLEM OF ZOOLOGICAL CLASSIFICATIONS AND THE TEACHING OF ZOOLOGY - BELTRAN, ENRIQUE (Laboratorio Fisiologia General y Vegetal, CD MEXICO, DF, MEX, 1947)
The de facto names commonly used for human malarial parasites should be officially accepted Plasmodium vivax is correct for the tertian parasite The quartan form should be termed P malariae (Grassi and Feletti, 1890) The malignant tertian parasite is
REV SOC MEX HIST NAT
Keywords: PROBLEM, ZOOLOGICAL CLASSIFICATIONS, TEACHING, ZOOLOGY; CIENCIAS DE LA VIDA; BIOLOGIA ANIMAL (ZOOLOGIA); ESTUDIO Y ENSEÑANZA